Surface reaction mechanism and characteristics of 2-dimensional TiO2 and 0-dimensional Ag nanocomposites specialized for H2S gas sensing at room temperature - Un Yup Lee; Min Young Kim; Kyu Hyoung Lee; Sol Han; Seung Yong Lee; Ali Mirzaei; Sun-Woo Choi; Myung Sik Choi; Changhyun Jin; Jeong Yun Hwang (Sensors and Actuators Reports)
In this study, we provide the synthesis of pristine TiO2 nanosheets (NSs) via a simple flux method and their decoration with Ag nanoparticles (NPs) using a hydrothermal method for room-temperature H2S gas sensing. Gas sensing experiments were conducted at 25 °C, evaluating the response of the Ag NPs-decorated TiO2 NSs to various gases. Results demonstrated the gas sensor exhibited a superior response to H2S gas compared to other gases, outperforming the pristine TiO2 NSs gas sensor. Additionally, its response to H2S gas surpassed that of the TiO2 NSs gas sensor, highlighting the promising role of Ag decoration for H2S gas detection. Sensing behavior in humid atmosphere was also investigated. The improved H2S gas sensing performance can be attributed to the catalytic effect of Ag, the formation of Ag/TiO2 heterojunctions, and the large surface area of the TiO2 NSs. This study introduces a straightforward approach to enhance the gas sensing capabilities of metal oxide NSs.